A Critical Review in University Teaching of Architecture. The Case of UNAM, Mexico and UNCUYO, Argentina - Miranda Gassull, Virginia (Universidad del Rosario, 2021)
The university plays a fundamental role in society and specifically in the configuration of human habitat. It starts from Architecture as a discipline that promotes practices, narratives and spatialities that modify our way of inhabiting the territories. The teaching of architecture is problematized in the way of exercising discipline, the citizens it prioritizes and the rationalization of the social space. It is proposed to analyze the socio-critical perspective in Latin American Architecture schools in order to recognize the ontoepistemic approach and the methodological design of the three functions of the University. Two architecture schools with different antiquities and on different urban scales (metropolis and megalopolis) are taken as a case study. As a result, the pedagogical proposals of two academic spaces that address the subject of human habitat in an integral way from Architecture are exposed, as a dialectical process between the needs of people and the configuration of the territories.